1997
DOI: 10.1046/j.1365-2958.1997.3651733.x
|View full text |Cite
|
Sign up to set email alerts
|

Action at a distance for glp repressor control of glpTQ transcription in Escherichia coli K‐12

Abstract: SummaryThe adjacent, divergently transcribed glpACB and glpTQ operons of Escherichia coli encode the anaerobic glycerol 3-phosphate dehydrogenase and glycerol 3-phosphate transporter/phosphodiesterase, respectively. These operons are negatively controlled by glp repressor binding to operators that overlap the glpA promoter elements. Using DNase I footprinting, three additional operators (O T 1-3) were identified at positions þ307 to þ359 within the glpT coding region. To assess a potential regulatory role for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…6B). The glpT transcriptional start site has been proposed to be an A residue 76 bases downstream of the translational start site; the site 1 element is located 36 bases upstream of the transcriptional start site (36). We confirmed that the proposed transcriptional start site is correct by 5= RACE analysis, as described in Materials and Methods (Fig.…”
Section: Torr-overexpressing Cells Have Limited Glycerol-3-phosphate supporting
confidence: 69%
“…6B). The glpT transcriptional start site has been proposed to be an A residue 76 bases downstream of the translational start site; the site 1 element is located 36 bases upstream of the transcriptional start site (36). We confirmed that the proposed transcriptional start site is correct by 5= RACE analysis, as described in Materials and Methods (Fig.…”
Section: Torr-overexpressing Cells Have Limited Glycerol-3-phosphate supporting
confidence: 69%
“…The genes comprising this regulon belong to five operons. Transcription of all but the glpEGR operon is negatively regulated by the glp repressor GlpR, a member of the DeoR family of transcriptional regulators (34,65,(69)(70)(71)(72). Operon glpACB, encoding the subunits of the anaerobic glycerol-P dehydrogenase, is located near min 51 of the E. coli genome (38).…”
mentioning
confidence: 99%
“…2). The binding of IHF to this site may bend the DNA to facilitate the formation of a complex structure that is involved in the inhibition of GlpT expression, mediated by the GlpR repressor in E. coli (28 In the glpTQ intergenic region, both Hib strains contained practically identical 1,428-bp sequences, except that HK695 contained one more tetrameric repeat (TTTA) in addition to the five repeats present in Eagan. The repeats were localized in a putative open reading frame (ORF) of 414 bp in HK695, designated ORF1 for these Hib strains (Fig.…”
mentioning
confidence: 99%
“…In E. coli and Bacillus subtilis (19), glpQ is transcribed together with glpT, which is located upstream of glpQ and encodes a G3P permease that acts as a G3P-inorganic phosphate antiporter (5). The E. coli glpTQ operon is induced by G3P and repressed by the catabolic repressor glucose as well as a glp-specific repressor protein, GlpR (28). Available restriction fragment length polymorphism (RFLP) data and DNA sequences of the glpTQ region of H. influenzae suggest that its organization differs between strains (7,13,24,25).…”
mentioning
confidence: 99%